Unclogging the Bottleneck: The role of case morphology in L2 acquisition at the syntax-discourse interface - Lecouvet, Mathieu; Degand, Liesbeth; Suner, Ferran (Language acquisition, 2021)
The Bottleneck Hypothesis argues that properties of inflectional morphology explain why second-language learners may face persistent difficulties in articulating meaning in target-language forms. In particular, the acquisition task proves even harder when first and second languages differ in the way they organize the mapping of functional features onto inflectional morphemes. Against this backdrop, the present study focuses on the interplay between case morphology and acquisition of syntax-discourse interface phenomena in the second language German of French native speakers. Whereas the Bottleneck Hypothesis predicts that discourse-driven syntactic alternations come for free when case morphology is in place, a concurrent prediction is made by the Interface Hypothesis, which suggests that the syntax-discourse interface is vulnerable per se, irrespective of L1-L2 differences at the interface between morphology and syntax. We tested 45 L2 learners in (i) a semicontrolled production task in context (element rearrangement task) targeting argument reordering (object fronting) as a function of the information status of discourse referents; (ii) a fill-in-the-blanks task involving the use of case endings; and (iii) a general proficiency test. Contra the Interface Hypothesis, results showed that argument reordering was affected by discourse properties of referents. Turning to the Bottleneck Hypothesis, learners' command of case was identified as a reliable predictor of convergence in discourse-to-syntax mappings, which confirms the key role of inflectional morphology in the acquisition of other grammar areas, including interfaces between grammar and grammar-external domains such as discourse.